PHILOSOPHICAL ANALYSIS OF THE ISSUES OF SOCIAL ORDER IN THE SYSTEM OF MODERN SOCIETY - Berdiyev Fazliddin Shobidinovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article conducts a scientific, theoretical, and philosophical analysis of the concept of modern society and its social order. It explores the conceptualization of the category of social order and delineates the primary components of social order in both traditional and modern societies within the context of socio-philosophical inquiries. Additionally, it investigates how the processes of monitoring and information regarding social changes influence the evolution of social order in modern